TIPOLOGI KODIFIKASI KITAB HADIS AL-MA’A - Kudhori, Muhammad (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
The method which is used by theologian in hadi> th codification has a trend that changes from time to time. After third century of hijriyah, some theologians arrange hadi>th?s book using the method that has already taught to them before, but others have a different method. One of the methods which is dissimilar from others is hadi>th codification method or it is called Mu?jam. Mu?jam is a hadi> th codification typology that is based on the friend of the Prophet?s Musnad or the writer?s teacher that is arranged based on the alphabet. In some sample, it has seemed that Mu?jam?s book also shows some friends of the Prophet?s biography before showing the history of them. Mu?jam?s book is classified into two groups. They are Mu?jam al-Shuyu>kh (based on teacher?s names) and Mu?jam al-Saha>bah (based on friends of the Prophet?s names). Commonly, there is some quality of hadi>th s in Mu?jam?s books. There are sahi>h, hasan, da?i>f even mawdu>? (false). One of the benefits in Ma?ajim?s book is as the main reference of Prophet?s Musnad hadi>th. It means continued until the Prophet himself and containing lots of hadi>th that is not found in al-Kutu>b al-Sittah. Moreover, Mu?jam?s book is one of the main references to know the biography of Sahabat (friend?s Prophet), nasab (offspring), and their virtue.